Alterations in coupling between global brain activity and cerebrospinal fluid flow in patients with insomnia disorder before and after transcranial direct current stimulation: a resting-state functional MRI study - Liu, Dehong; Chen, Xin; Zhang, Xiaotong; Peng, Jiaqi; Zhou, Hongwei; Lan, Wenjing (Frontiers in Psychiatry, 2025)
BackgroundThe coupling between global blood-oxygen-level-dependent (gBOLD) signals and cerebrospinal fluid (CSF) flow has been established in humans and is thought to reflect the function of the brain’s glymphatic system. This study aimed to investigate glymphatic system dysfunction in insomnia disorder (ID) and its correlation with clinical symptoms, and to evaluate whether transcranial direct current stimulation (tDCS) can modulate glymphatic system and alleviate insomnia.MethodsWe totally enrolled 33 IDs (20 females, 42.3±15.0 years) and 27 healthy controls (HCs, 15 females, 53.6±17.7 years). Among them, 19 IDs (9 females, 38.4±16.1 years) received 2-week tDCS treatment. gBOLD-CSF coupling strength was compared between groups and correlated with clinical scale scores (PSQI, PHQ-9, GAD-7). Changes in gBOLD-CSF coupling strength and clinical scores after tDCS were also examined.ResultsIDs showed significantly weaker gBOLD–CSF coupling than HCs (p=0.003). Coupling strength was negatively correlated with PSQI score (r=-0.363, p=0.045) and GAD-7 score (r=-0.435, p=0.014), but not with PHQ-9. After tDCS, patients exhibited significantly reducing in PSQI score(p=0.014), GAD-7 score (p=0.0001) and PHQ-9 score (p<0.0001), along with increasing in gBOLD-CSF coupling strength (p=0.002).ConclusionOur results indicate that IDs exhibit impaired glymphatic system function, as reflected by reduced gBOLD–CSF coupling strength. This reduction was correlated with the severity of both insomnia and anxiety symptoms. Moreover, we demonstrated that tDCS can not only improve symptoms of insomnia, anxiety, and depression but also enhance glymphatic activity in IDs.